Heat transfer and flow characteristics of microchannels with solid and porous ribs. (September 2020) - Li, Fei; Ma, Qingming; Xin, Gongming; Zhang, Jingchao; Wang, Xinyu
Highlights: The solid and porous ribs can improve the thermal performance of microchannels. The pressure drops with porous ribs are smaller than those with solid ribs. The field synergy effect with porous ribs is better than that with solid ribs. The microchannels with symmetrical and staggered porous ribs show the best PEC . Abstract: The microchannel cooling technology is an effective method to solve heat dissipation problems caused by high power electronic devices. In this work, the heat transfer and flow characteristics of microchannels with solid and porous ribs are comprehensively investigated using numerical approaches. It is reported that the thermal performance of microchannels with solid and porous ribs are significantly better than those without any ribs. The field synergy principle is adopted to analyze the thermal performance, which proves that microchannels with porous ribs show a better synergy effect compared to those with solid ribs. On the other hand, the pressure drops and friction factors for all microchannels with solid ribs are larger than those with porous ribs. When solid ribs are replaced by porous ribs, the pressure drops reduce about 67%, 57% and 12% for the middle, symmetrical and staggered rib configurations, respectively. It can be found that vortices and recirculation flow come into being behind solid ribs. The thermal boundary layers are disrupted and redeveloped due to the intensified fluid mixing in porous regions, which facilitates the convective heat transfer. Finally, the comprehensive thermal and hydraulic performance is evaluated, and microchannels with symmetrical and staggered porous ribs exhibit the best comprehensive thermal and hydraulic performance.